2022
DOI: 10.3389/fimmu.2022.867229
|View full text |Cite
|
Sign up to set email alerts
|

Immunopsychiatry – Innovative Technology to Characterize Disease Activity in Autoantibody-Associated Psychiatric Diseases

Abstract: Background Anti-neural autoantibody-associated psychiatric disease is a novel field in immunopsychiatry that has been attracting attention thanks to its potentially positive therapeutic outcome and distinct prognosis compared with non-organic psychiatric disease. This review aims to describe recent novel technological developments for improving diagnostics in the field of autoantibody-related psychiatric disease.MethodsWe screened for relevant articles in PubMed for this narrative article. We focused on resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Considering the relationship between the neuronal plasticity (or synaptic function) and the pathology of MDD, a thorough understanding of the response to inflammation in the brain is important. Several recent studies have suggested that among many environmental factors, inflammation and immune abnormalities in the brain and peripheral tissues are associated with the onset of neuropsychiatric disorders, and inflammation during brain development has been shown to strongly increase the risk of MDD [Goldsmith et al, 2016;Pape et al, 2019;Abdoli et al, 2020;World Health Organization (WHO), 2020;Hansen, 2022;Wang et al, 2022]. In addition, synaptic pruning is induced by increased reactive microglia in the brain of patients with MDD, and nonsteroidal anti-inflammatory drugs (NSAIDs) perform assistant functions in enhancing the therapeutic effects in patients with senile depression (Wohleb et al, 2016;Yuan et al, 2020;Hang et al, 2021;Dawood et al, 2022;Strekalova et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the relationship between the neuronal plasticity (or synaptic function) and the pathology of MDD, a thorough understanding of the response to inflammation in the brain is important. Several recent studies have suggested that among many environmental factors, inflammation and immune abnormalities in the brain and peripheral tissues are associated with the onset of neuropsychiatric disorders, and inflammation during brain development has been shown to strongly increase the risk of MDD [Goldsmith et al, 2016;Pape et al, 2019;Abdoli et al, 2020;World Health Organization (WHO), 2020;Hansen, 2022;Wang et al, 2022]. In addition, synaptic pruning is induced by increased reactive microglia in the brain of patients with MDD, and nonsteroidal anti-inflammatory drugs (NSAIDs) perform assistant functions in enhancing the therapeutic effects in patients with senile depression (Wohleb et al, 2016;Yuan et al, 2020;Hang et al, 2021;Dawood et al, 2022;Strekalova et al, 2022).…”
Section: Introductionmentioning
confidence: 99%